Research of the influence of power engineering equipment accident rate on the indicators of adequacy and the value of operating reserve of electrical power system - Krupenev Dmitry (E3S Web of Conferences, 2020)
Reliable source information is necessary for a correct adequacy assessment of electric power systems. Among a wide set of initial information, coefficients of accident rates of power engineering equipment are important. The analysis of methods for determining the coefficients of accident rates of power engineering equipment, which are used in the assessment of the adequacy of electric power systems, is presented in the article, also the features of accounting for coefficients of accident rates are elicited. The experimental part of the article is showed the influence of generating aggregates accident rate on the level of operating reserve on the example ofthe Unified Energy System of Russia.